An Acoustic Study of the Emphatic Occlusive [ṭ] in School-Going Children with Cleft Palate or Cleft Lip - BAAZI, Khaled; GUERTI, Mhania (Archives of Acoustics, 2022)
The aim of this acoustic study is to analyse the phoneme [ṭ] produced by school children surgically operated on for the cleft palate or cleft lip, in order to examine their vocal characteristics, to provide speech therapists with numerous concrete analyses of voice and speech, to effectively support them and to prevent some serious outcomes on their psychological and academic development. The motivation for this study was mainly stemming from the difficulties that Algerian schoolchildren with clefts encounter in the pronunciation of this phoneme. To carry out the study, several acoustic parameters were investigated in terms of the fundamental frequency F0, the first three formants F1, F2, and F3, the energy E0, the Voice Onset Time (VOT), the durations [CV] and [V] of the subsequent vowel [a]. For the analysis, further important parameters in the field of pathological speech were deployed, namely the degree of disturbance of F0 (jitter), the degree of disturbance of intensity (shimmer) and the HNR (Harmonics to Noise Ratio). Results revealed disturbance in the values of F1, F2, and F3 and stability in the values of F0. Another important reported aspect is the increase in the value of the VOT due to the difficulties in controlling the plosives’ successive closure and release.